2013
DOI: 10.1371/journal.pone.0057158
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution between Male and Female Genitalia in the Drosophila melanogaster Species Subgroup

Abstract: In contrast to male genitalia that typically exhibit patterns of rapid and divergent evolution among internally fertilizing animals, female genitalia have been less well studied and are generally thought to evolve slowly among closely-related species. As a result, few cases of male-female genital coevolution have been documented. In Drosophila, female copulatory structures have been claimed to be mostly invariant compared to male structures. Here, we re-examined male and female genitalia in the nine species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(145 citation statements)
references
References 58 publications
(84 reference statements)
3
141
0
1
Order By: Relevance
“…The posterior lobe is a hook-shaped outgrowth unique to the external genitalia of D. melanogaster and its closest relatives in the melanogaster clade (Figure 1) (Jagadeeshan and Singh, 2006; Kopp and True, 2002). A cuticular projection similar to the posterior lobe is also present in the yakuba clade (Yassin and Orgogozo, 2013), suggesting a recent origin of this structure in the melanogaster subgroup (Figure S1). Among members of the melanogaster clade, the posterior lobe is highly divergent in shape and size, and represents the only reliable character to distinguish species identity (Coyne, 1993).…”
Section: Resultsmentioning
confidence: 90%
“…The posterior lobe is a hook-shaped outgrowth unique to the external genitalia of D. melanogaster and its closest relatives in the melanogaster clade (Figure 1) (Jagadeeshan and Singh, 2006; Kopp and True, 2002). A cuticular projection similar to the posterior lobe is also present in the yakuba clade (Yassin and Orgogozo, 2013), suggesting a recent origin of this structure in the melanogaster subgroup (Figure S1). Among members of the melanogaster clade, the posterior lobe is highly divergent in shape and size, and represents the only reliable character to distinguish species identity (Coyne, 1993).…”
Section: Resultsmentioning
confidence: 90%
“…A genetic covariance exists between male damage and female susceptibility to damage exists in this species as evidenced by a full sib/half sib design (Gay et al 2011). A recent comparative study in the Drosophila melanogaster species complex, revealed previously unknown internal and external female adaptations some of which appear to counteract or prevent the damage cause by male genital structures, therefore likely evolving by SAC, whereas others seeming to facilitate copulation, therefore evolving by female choice (Yassin and Orgogozo 2013).…”
Section: Examples Of Genital Coevolution Insectsmentioning
confidence: 99%
“…For example, female genitalia in Drosophila were deemed to be fairly invariant across species (Eberhard and Ramirez 2004;Jagadeeshan and Singh 2006), but a recent study showed that in nine species of Drosophila, several aspects of female genital morphology covary with male genital traits ( Fig. 2) (Yassin and Orgogozo 2013). A geometric morphometric analysis of genital shape among two sister species of water snakes (Nerodia sp.)…”
Section: For a Lock-and-key Mechanism To Prevent Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Females in the melanogaster group show a pattern of sclerotized structures that are hypothesized to function as a resistance adaptation (Kamimura and Mitsumoto 2011;Yassin and Orgogozo 2013). Correspondingly, interspecific matings between the sister species Drosophila santomea and Drosophila yakuba resulted in more damaging CW than in intraspecific matings (Kamimura 2012).…”
Section: Drosophila: Fruit Fliesmentioning
confidence: 99%